Implementation of Indigenous Food Strategies and the Role of Local Wisdom in Papua's Food Sovereignty - Saa, Septinus (Arbain Publishing, 2025)
This study explores the implementation of indigenous food strategies and the role of local wisdom in Papua’s food sovereignty, Indonesia. Papua, known for its rich cultural diversity and unique ecological environment, has long depended on indigenous food systems that are in harmony with nature. These food systems, embedded in local traditions and customs, offer valuable insights into sustainable food practices. By utilizing a qualitative research approach, this study primarily relies on library research and a comprehensive review of existing literature to examine the interconnections between indigenous food strategies, local knowledge, and food sovereignty. The research identifies key indigenous practices that support food security, such as the preservation of traditional crops, resource management, and community-based food systems. It further highlights how these practices have been influenced by local wisdom and their potential to enhance food sovereignty in Papua amidst global challenges like climate change and food insecurity. The findings suggest that integrating indigenous food strategies with modern agricultural practices could offer a sustainable path forward for achieving food sovereignty in Papua. Moreover, the study underscores the importance of preserving indigenous knowledge as a means to strengthen resilience and self-sufficiency in the region. This research contributes to a broader understanding of the role indigenous food systems play in ensuring food sovereignty, with implications for policy-making and sustainable development in Papua and beyond.